Clausal and DP-internal agreement in Ikalanga - Rose Letsholo (LibraryPress@UF, 2004)
This paper investigates the controversial morphemes that occur both at the clause level and within the DP in Bantu languages such as Ikalanga, which have been analyzed as "agreement morphology" by some (Baker 2002, Demuth and Harford (1999) and as resumptive/incorporated pronouns by others (Bresnan and Mchombo 1987, Zwart 1997). The paper proposes a unified analysis of this phenomenon, analyzing both clausal and DP-internal occurrences of these morphemes as agreement morphology which holds between the head of an XP and its predicate, or between the head of an XP and its modifiers. In both instances, the agreement relation is instantiated after movement of the relevant category from its base position to a specifier position which enables the moved category to enter into a checking relation (i.e. a spec-head configuration) with another category that has matching features (Chomsky 1995).